2013
DOI: 10.1177/0004867413478217
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in bipolar disorder: A positional paper from the International Society for Bipolar Disorders Biomarkers Task Force

Abstract: Although the etiology of bipolar disorder remains uncertain, multiple studies examining neuroimaging, peripheral markers and genetics have provided important insights into the pathophysiologic processes underlying bipolar disorder. Neuroimaging studies have consistently demonstrated loss of gray matter, as well as altered activation of subcortical, anterior temporal and ventral prefrontal regions in response to emotional stimuli in bipolar disorder. Genetics studies have identified several potential candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
142
4
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(157 citation statements)
references
References 145 publications
(148 reference statements)
3
142
4
8
Order By: Relevance
“…[1,3] Our review provides a summary of preliminary findings about the link between inflammatory processes, decreased neurotrophins, increased oxidative stress and juvenile or young adult age BD. Two different lines of research have been pursued in this field, one regarding early onset (pediatric) of BD and the other on the effects of course variables (duration of illness, number of episodes, hospitalizations) on changes in inflammatory markers, neurotrophins and markers of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,3] Our review provides a summary of preliminary findings about the link between inflammatory processes, decreased neurotrophins, increased oxidative stress and juvenile or young adult age BD. Two different lines of research have been pursued in this field, one regarding early onset (pediatric) of BD and the other on the effects of course variables (duration of illness, number of episodes, hospitalizations) on changes in inflammatory markers, neurotrophins and markers of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…[1,11] Furthermore, adult subjects with BD are at higher risk of developing comorbid medical illnesses such as diabetes, metabolic and cardiovascular diseases that are also associated with elevated levels of proinflammatory markers. [12,13] Potentially involved cytokines include tumor necrosis factor (TNF), interleukin-2 (IL-2), IL-6, IL-8, IL-13 and apolipoprotein A1.…”
Section: Introductionmentioning
confidence: 99%
“…1 As consistently found in postmortem studies, in BD, morphological alterations are associated with disruption of cerebral functions, leading to impairment in the cellular plasticity and resilience of the brain. 2 Currently, many studies have reported alterations in the morphology of brain tissues, brain cells, and in the periphery. These alterations could be directly correlated to dysregulation of the molecular pathways of inflammation and neurotrophins.…”
Section: Introductionmentioning
confidence: 99%
“…For several years, brain derived neurotrophic factor (BDNF) has been one of the most studied neurotrophins in BD (16). Recent studies reported decreased BDNF and increased glia-derived neurotrophic factor (GDNF) levels in both mania and depression (17), increased GDNF/BDNF ratio in mania (18), and increased GDNF levels during manic switch due to ECT (19) confirming the role of the disrupted supportive cellular network in BD.…”
mentioning
confidence: 98%